2018
DOI: 10.1080/00365513.2018.1423702
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for diagnosing chronic myelomonocytic leukemia using structural parameters of Sysmex XNTM analyzers in routine laboratory practice

Abstract: According to WHO recommendations, diagnosis of chronic myelomonocytic leukemia (CMML) beforehand requires microscopic examination of peripheral blood to identify dysplasia and/or blasts when monocytes are greater or equal to 1.0 × 10/L and 10% of leucocytes. We analyzed parameters derived from Sysmex XN analyzers to improve the management of microscopic examination for monocytosis. We analyzed results of the complete blood count and the positioning and dispersion parameters of polymorphonuclear neutrophils and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…2 Blood smear examination is the first step to distinguish neoplastic conditions in patients with AMC equal to or higher than 1.0 10 3 /µL and 10% of white blood cell (WBC) count. 3 However, blood smear examination is not necessary in a patient with reactive monocytosis unless there is a different flag on the complete blood count (CBC) analysis. 4 Schillinger et al 3 found that the use of the "mono-dysplasia-score" calculated on Sysmex XN series of blood count analyzers was effective in the early diagnosis of CMML and in reducing the unnecessary blood smear examinations in reactive monocytosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Blood smear examination is the first step to distinguish neoplastic conditions in patients with AMC equal to or higher than 1.0 10 3 /µL and 10% of white blood cell (WBC) count. 3 However, blood smear examination is not necessary in a patient with reactive monocytosis unless there is a different flag on the complete blood count (CBC) analysis. 4 Schillinger et al 3 found that the use of the "mono-dysplasia-score" calculated on Sysmex XN series of blood count analyzers was effective in the early diagnosis of CMML and in reducing the unnecessary blood smear examinations in reactive monocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, blood smear examination is not necessary in a patient with reactive monocytosis unless there is a different flag on the complete blood count (CBC) analysis. 4 Schillinger et al 3 found that the use of the "mono-dysplasia-score" calculated on Sysmex XN series of blood count analyzers was effective in the early diagnosis of CMML and in reducing the unnecessary blood smear examinations in reactive monocytosis. This score is calculated with AMC, neutrophil/monocyte ratio, and neutrophil distributions with a monocyte count equal to or higher than 1.0 10 3 / µL and 10% of the WBC count in adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ne‐WX detects moderate dysgranulopoiesis, even in cases where morphological abnormalities visible by microscopic examination are minimal, constituting a useful tool in the cytological analysis of dysplasia. This parameter has already been shown to be of value in the screening for chronic myelomonocytic leukaemia (Schillinger et al , ).…”
Section: Discussionmentioning
confidence: 97%
“…Monoscore was automatically calculated for all samples falling within the WHO criteria. No intersite reanalysis was carried out since the previous Schillinger et al study already demonstrated that the score performance in such conditions was not analyzer‐dependent. As previously published, a Monoscore ≥0.161 was considered as an abnormal result suggesting increased probability of CMML.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the low frequency of CMML (0.4 cases per 100 000 population), the International Society for Laboratory Hematology and the Groupe Francophone d'Hématologie Cellulaire (GFHC) both recommended a blood smear review if the monocyte count exceeds 1.5 × 10 9 /L on the first CBC or if monocytosis persists for more than 30 days in adult patients to avoid an excess of unnecessary smear reviews, reducing the rate to 1.2% . In a recent study, using structural parameters of the Sysmex XN™ analyzers, we described the “mono‐dysplasia‐score” also referred to as “Monoscore.” This score incorporated three parameters: neutrophil/monocyte ratio, structural neutrophil dispersion (Ne‐WX), and monocyte absolute count and was calculated as soon as the WHO criteria were met (monocyte count ≥ 1 × 10 9 /L and monocytes accounting for ≥10% of the WBC count). Structural neutrophil dispersion is increased in the presence of hypogranulated/degranulated neutrophils, a hallmark of dysplasia in the context of CMML, while the neutrophil/monocyte ratio shows evidence of monocytic proliferation outside of an infectious context.…”
Section: Introductionmentioning
confidence: 99%